Rational manipulation of lattice strain to tailor the electronic and optical properties of nanostructures. Issue 22 (15th November 2021) - Xie, Ruishi; Guo, Zhicheng; Li, Xuhai; Liu, Haifeng; Sun, Hongjuan; Guo, Baogang; Liu, Qinghua; Li, Yuanli
Abstract: Optoelectronic devices with different energy ranges requires materials with different band gaps, sometimes even within the same device. Structural distortions within the nanostructures produce lattice strains, which can change physical properties. However, the detailed knowledge of lattice strains in nanostructures remains confusing. Here, we rationally design and employ a simple and effective scheme to fabricate strained BiVO4 /ZnS nanostructures. Lattice strain originates from lattice distortion caused by the intentional incorporation of metal ions into the inner layer of nanostructures. Experimental findings show that the maximum and minimum band gap energies of BiVO4 /ZnS nanostructures are 2.87 and 2.79 eV under the tensile strain, which are increased by 4.4% and 1.4%, respectively, compared with that of the reference sample (2.75 eV). Impressively, BiVO4 /ZnS nanostructures exhibit tunable dual emission behavior, and lattice strain significantly changes the electron band structure of the nanostructures. In addition, we identify the composite structure of BiVO4 /ZnS nanomaterials and elucidate the mechanistic origin of regulation of the optical and electronic properties by lattice strain in combination with experimental and density functional theory calculations. These results provide a deep understanding of the relationship between lattice strain and optical properties and indicate that strain engineering can be potentially used in the design of nanostructures.